Intracisternal administration of Mycobacterium tuberculosis potentiates the delayed type hypersensitivity in guinea-pigs - Niedermayerová-Roucová, I; Hude, P; Strnadová, V; Gulda, O (Physiologia Bohemoslovaca, 1990)
The delayed type hypersensitivity (DTH) was studied in guinea-pigs using the skin test. The mycobacterium tuberculosis (M. tbc)--was applied by various routes. The control group received ovalbumin in Freund's incomplete adjuvant (FIA) into the footpad. The first experimental group received ovalbumin in Freund's complete adjuvant (FCA) into the footpad. The other experimental groups always received, in addition to ovalbumin plus FIA into the footpad, the M. tbc. 1. intracisternally, 2. intramuscularly, 3. intraperitoneally, 4. orally. On the day of administration of the sensibilizing substance, the body temperature was monitored. The skin test was measured after 14 and 21 days. It was established that, for the study of the DTH, the 21-day interval was more significant than the 14-day interval. A 100 times smaller dose of M. tbc. given intracisternally had the same immunostimulating effect as the injection of ovalbumin with M. tbc into the footpad (p less than 0.01). The size of the skin reaction was not only significantly influenced by the intramuscular and oral administration of M. tbc. On the other hand, the intraperitoneal administration inhibited the DTH (p less than 0.01). The increase of body temperature after the administration of M. tbc. correlated with the influence on the DTH except for the intraperitoneal administration. The route of the M. tbc. administration was crucial for the development of the DTH.
Keywords: morčata; Skin Tests; Body Temperature; tělesná teplota; Animals; pozdní přecitlivělost; kožní testy; Guinea Pigs; zvířata; Hypersensitivity, Delayed; Mycobacterium tuberculosis